Rancang Bangun Sistem Informasi Akuntansi Penerimaan Kas Berbasis Web pada SMP dan SMA Villa Mas - Pirnando, Pirnando; Purwohedi, Unggul; Armeliza, Diah (Ekopedia: Jurnal Ilmiah Ekonomi, 2026)
This study aims to design and build a web-based accounting information system for cash receipts at SMP and SMA Villa Mas. The research uses a qualitative approach with Research and Development (R&D) method and the Waterfall model for system development, consisting of requirement analysis, design, coding, and testing stages. Data were collected through observation, interviews, documentation, and literature study with informants including the treasurer, administration staff, and school principal. The results show that the manual cash receipt system using ledgers and Microsoft Excel causes various problems such as data integration issues, difficulty tracking student payment status, double recording, calculation errors, difficulty finding payment history, slow report preparation, and inefficient archiving. Based on these problems, a web-based system was designed with features for managing master data (students, classes, majors, school units, academic years, fee types, and rates), generating student bills, payment transactions, printing receipts, displaying student bill recaps, and generating cash receipt reports. System testing using Black Box Testing method shows that all system functions run according to user needs. The system is declared feasible for use and can improve the efficiency, accuracy, and transparency of cash receipt administration at SMP and SMA Villa Mas.